2019
DOI: 10.3390/ma12050801
|View full text |Cite
|
Sign up to set email alerts
|

Flame-Retardant Mechanism of Layered Double Hydroxides in Asphalt Binder

Abstract: The flame retardancy of asphalt binders with layered double hydroxides (LDHs) was investigated using limiting oxygen index (LOI) and cone calorimeter tests. The flame-retardant mechanism of the LDHs was also studied with thermogravimetry and differential scanning calorimetry (TG–DSC), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). The cone calorimeter testing results indicated that 2 wt.% of the LDHs can decease the peak heat and smoke release rate of asphalt binders. Because a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Recently, in Zhu et al . research study, LDH as FR in asphalt binders was investigated using limited oxygen index (LOI) and cone calorimeter test. ZnMgAl‐CO 3 ‐LDHs synthetic with specific surface area of 13.2 m 2 /g and a purity of 99.0% were used as FR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in Zhu et al . research study, LDH as FR in asphalt binders was investigated using limited oxygen index (LOI) and cone calorimeter test. ZnMgAl‐CO 3 ‐LDHs synthetic with specific surface area of 13.2 m 2 /g and a purity of 99.0% were used as FR.…”
Section: Introductionmentioning
confidence: 99%
“…ZnMgAl‐CO 3 ‐LDHs synthetic with specific surface area of 13.2 m 2 /g and a purity of 99.0% were used as FR. The FR asphalt was prepared by melt blending, containing 2, 5, 10, and 25 wt % of LDH . Cone calorimeter testing shows that 2 wt % of LDH decreases the peak heat release rate (PHRR) and smoke release rate of asphalt binders; this result can be explained due to the good dispersion of the low dose of LDH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDHs can be directly used as ame retardant additives because of their unique chemical properties and layered structures [170][171][172][173][174][175][176][177]. For example, exible polyurethane foam with samples containing 10% ame retardant, the LOI increased from 20.8 to 29.0, the UL-94 rating increased from no to V-0, and the pHRR decreased from 1090 to 284 kW/m 2 , respectively.…”
Section: Silicon-containing Compoundsmentioning
confidence: 99%
“…LDHs have chemical composition tunability and interlayer anion exchangeability, which endow them with unique properties and functions. Therefore, LDHs have a wide range of applications in many fields, such as catalysts [6], adsorbents [7], corrosion protection [8], and flame-retardant materials [9,10]. Some studies have shown that LDH can absorb a large amount of heat, dilute the concentration of flammable gas, and absorb harmful acid gases during the decomposition process; therefore, it is an excellent flame retardant [11].…”
Section: Introductionmentioning
confidence: 99%